Action of ethylene on postharvest of summer squash ‘Menina Brasileira’ - de Araújo, Fernanda Ferreira; da Costa, Lucas Cavalcante; da Silva, Tania Pires; Puiatti, Mário; Finger, Fernando Luiz (Revista Ceres, 2017)
The purpose of this study was to evaluate the sensitivity and the physiological responses of summer squash ‘Menina Brasileira’ to ethylene. Immature fruits were harvested and placed in 20 L sealed buckets, in which ethylene was applied at concentrations of 0.1, 1.0, 10, 100, and 1000 μL L-1 for 24 h. Fruits were placed in buckets with no ethylene as a control treatment. Thereafter, the fruits were taken out of the buckets and maintained on bench, wherein on days 0, 2, 4, 6, and 8, they were evaluated regarding the accumulated fresh weight loss, soluble sugars, reducing and non-reducing sugars, starch, total chlorophyll, content of malondialdehyde, and electrolyte leakage. Fruits of summer squash ‘Menina Brasileira’ showed sensitivity to exogenous ethylene with no weight loss stimulation. Additionally, the fruits exhibited small changes in nutritional quality attributes and changes in the external fruit appearance, including decreased chlorophyll content as well as damage to cell membrane characterized by increase in malondialdehyde content and electrolyte leakage. These changes were stimulated by increasing exogenous ethylene concentration.